Persecution, Pogroms and Genocide: A Conceptual Framework and New Evidence - Sascha O. Becker; Sharun Mukand; Ivan Yotzov (Center for Economic Studies and ifo Institute (CESifo), 2022)
Persecution, pogroms, and genocide have plagued humanity for centuries, costing millions of lives and haunting survivors. Economists and economic historians have recently made new contributions to the understanding of these phenomena. We provide a novel conceptual framework which highlights the inter-relationship between the intensity of persecution and migration patterns across dozens of historical episodes. Using this framework as a lens, we survey the growing literature on the causes and consequences of persecution, pogroms, and genocide. Finally, we discuss gaps in the literature and take several tentative steps towards explaining the differences in survival rates of European Jews in the 20th century.
Keywords: D74; F22; F51; N40; O15; R23; 330; genocide; persecution; migration; immigration restrictions; exit or voice